Reorienting the Manchus : A Study of Sinicization, 1583-1795 - Huang, Pei, 1928- (Book collections on Project MUSE., 2011)
"Making extensive use of Chinese, Japanese, Manchu, and Western sources, the author adopts a historical multifaceted approach to explore the various forces geography, economics, frontier contacts, political and social institutions; language, literature and art; religion and Confucianism that made possible the Manchu adoption of Chinese ways of life."--Publisher's description.